English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-11-28 12:24:06 · 7 answers · asked by Kamikaze Pilot 2 in Science & Mathematics Mathematics

Find the solution to the following linear non-homogeneous differential equation of the first order if y(0)=0.

2006-11-28 12:27:46 · update #1

7 answers

dy/dx+2y=2, if y(0)=0

dy/dx=2-2y=2(1-y)
dy/(1-y)=2dx
integrate
-ln(1-y)=2x+C{C is a constant}
ln(1-y)= -2x-C
take'e'
1-y= e^(-2x-C)
y= 1-e^(-2x-C)
take initial conditions
0=1-e^(-C)
>>>>>C=0
therefore,y=1-e^(-2x)

check in original equation
dy/dx=2e^(-2x)
2y=2-2e^(-2x)
dy/dx+2-2e^(-2x)=2
solution agrees with original
equation,therefore it is
correct

2006-11-28 20:21:04 · answer #1 · answered by Anonymous · 0 0

dy/dx + 2y = 2
dy/dx = 2 - 2y
Integral of (1/2-2y)dy = Integral dx
[ln(2-2y)]/(-2) = x + c
ln(2-2y) = -2x + C

Since y(0)=0, then
ln2 = C

So,
ln(2-2y) = -2x + ln2
ln(2-2y) - ln2 = -2x
ln[(2-2y)/2] = -2x
ln[2(1-y)/2] = -2x
ln(1-y) = -2x
1 - y = e^(-2x)
1 - e^(-2x) = y

2006-11-28 12:42:54 · answer #2 · answered by Kemmy 6 · 0 0

dy/dx=2(1-y)
dy/(1-y)= 2dx
integrate both sides
ln(1-y) =-2x+const
or e^-(2x+const)=1-y
> y=1-e^(-2x) if const of int=0 since 1-e^0e^const=0
Missed neg sign!

2006-11-28 12:48:42 · answer #3 · answered by troothskr 4 · 0 0

Still doesn't make any sense.

2006-11-28 12:26:04 · answer #4 · answered by Jazz 4 · 0 0

dy/(1-y) = 2dx
-log(1-y)=2x
1-y = e^(-2x)
y=1 - e^(-2x)

2006-11-28 12:28:03 · answer #5 · answered by Rajkiran 3 · 1 0

Where the fcuk did "e" come from then ?

2006-11-28 12:37:37 · answer #6 · answered by Anonymous · 0 0

i c u p o k

2006-11-28 12:46:45 · answer #7 · answered by a m 4 · 0 0

fedest.com, questions and answers